Law Compliance and Prevention and Control of Illegal Activities in the Forest Sector in Guyana : Preliminary Report Prepared for the World Bank - Clarke, Gary (World Bank, Washington, DC, 2021)
Guyana is the only English speaking country in South America, is located on the Atlantic seaboard of north-eastern South America. It extends 800 km south from latitude 88 degree N on the Atlantic coast to latitude 1 degree N and some 480 km east to west between longitudes 57 degree and 61 degree W. It has an area of about 215,000 km. The total population is some 750,000 made of 45 percent Indian descent, 37 percent Afro-Caribbean, 7 percent Amerindian and 11 percent of Chinese, European, and mixed descent. Population and commercial agriculture is concentrated along the coastal strip. In 2004 Guyana had a Gross National Income per capita of US$990 (globally ranked 146th) according to World Bank data. Other sectors involved in the custody of the land and natural resources have also received considerable support during the same period. The key sector agencies involved in natural resource management, the Guyana Forestry Commission (GFC), the Guyana Geology and Mines Commission and the Guyana lands and surveys commission, are working on a long-term collaboration to develop a national land use plan for Guyana. In the short-term, the agencies are reaching an understanding and accord on land management particularly where resources overlap and exploitation can cause intersectoral conflicts (such as gold-mining and forestry).